Pendampingan Percepatan Penurunan Stunting Melalui Pemberdayaan Masyarakat untuk Mengolah Kelimpahan Lele di Desa Batu Kumbung - Fitria, Baiq; Wayan Canny Naktiany; Hasbullah; Febriana Wenny Wijaya (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
Abstract: This community service activity aims to find solutions for problems faced by the people of Batu Kumbung Village in improving family economy, by making various processed products based on local food (catfish). Fresh water fishery products found in Batu Kumbung Village are very abundant, especially catfish. The people of Batu Kumbung Village already have a joint business group, but the products produced are still very limited. In this regard, then it is necessary to provide catfish water processing skills to the community in Batu Kumbung Village so that it is expected to increase knowledge and skills that can used to improve the economy. Methods used in this activities, are: Providing training material modules to be implemented; The presentation of the material is in accordance with the contents of the recipe book plus material on food nutrition, hygiene and sanitation, kitchen management, and product packaging and online marketing related to the business to be run. The output target of the activity is that participants can increase their knowledge and skills in producing various catfish; Participants are able to organize and manage the business them properly and sustainably; the presence of a variety of local food-based specialty preparations which can be used as souvenirs for consumers..